Exponential Lagrange Stability for Markovian Jump Uncertain Neural Networks with Leakage Delay and Mixed Time-Varying Delays via Impulsive Control. (20th June 2018) - Yogambigai, J.; Syed Ali, M.; Zhu, Quanxin; Cai, Jingwei
Abstract : The problem of exponential Lagrange stability analysis of Markovian jump neural networks with leakage delay and mixed time-varying delays is studied in this paper. By utilizing the Lyapunov functional method, employing free-weighting matrix approach and inequality techniques in matrix form, we establish several novel stability criteria such that, for all admissible parameter uncertainties, the suggested neural network is exponentially stable in Lagrange sense. The derived criteria are expressed in terms of linear matrix inequalities (LMIs). A numerical example is provided to manifest the validity of the proposed results.